PRESENTATIONS OF MECKEL'S DIVERTICULUM AT KHYBER TEACHING HOSPITAL PESHAWAR - Rehman, Inayat ur; Burki, Tariq; Alam, Said; Rahman, Fazl e (Journal of Ayub Medical College Abbottabad, 2003)
Background: This study was conducted with an objective to observe various presentations of Meckel's Diverticulum in our setting and compare it with other national and international studies. Methods: It was a retrospective analysis of hospital record carried out at the department of paediatric surgery Khyber Teaching Hospital, Peshawar. A total of 63 patients meeting the inclusion criteria were included in the study who had presented to our unit with signs and symptoms of Meckel's Diverticulum and who were diagnosed either by investigations or at surgery. All the patients were explored and resection and anastomosis performed. We did not do H. Pylori culture. Patients with bleeding per rectum were investigated by Meckel's scan. Analysis of the results was done by SPSS version 10. Results: Majority of our patients presented with obstruction (82.5%) in contrast to the Western studies (around 40%) while only 4.7% presented with bleeding per rectum again in contrast to the Western countries (38-56%). Conclusion: There appears to be a geographical and/or racial difference in the presentation of Meckel's diverticulum.